Cutting tool feed drive of wafer background milling machine - E. S. Gebel; A. Yu. Popov; I. N. Drozdov (Омский научный вестник)
The paper describes the process of designing the cutting tool feed drive of a special metalworking machine, which due to the circuit solution and automatic control system will increase the productivity of processing one cell of wafer background on sheet material up to 10–15 seconds. On the basis of the analysis of the technology of milling of a given regular pattern of wafer background and peculiarities of the equipment operation it proposed to replace the traditional ball bearing gear in the cutting tool feed drive with a flat combined crank-slide mechanism. Geometrical parameters of the lever transmission mechanism calculated in accordance with the known dimensions of the regular cell pattern and the recommended value of the angle of motion transmission. The analysis of kinematic and power characteristics of the lever mechanism allowed to justify the technical characteristics of the electric motor. In order to realize the required trapezoidal law of the output link speed change, the inverse problem of kinematics solved, numerical values of the instantaneous angular velocity of the input crank and pulse control signals to the servomotor obtained.